2004
DOI: 10.1210/en.2004-0496
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Signal-Regulated Kinases Are Involved in the Acute Activation of Steroidogenesis in Immature Rat Leydig Cells by Human Chorionic Gonadotropin

Abstract: We studied the involvement of the ERK cascade in human chorionic gonadotropin (hCG)-induced steroidogenesis by primary cultures of immature rat Leydig cells. Our findings indicate that protein kinase A and protein kinase C function as upstream kinases in connection with transduction of the signal from the gonadotropin receptor to the ERK cascade. These MAPKs enhance the stimulatory effects of hCG on the de novo synthesis of the steroidogenic acute regulatory protein and the activity of protein phosphatase 2A, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
73
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(83 citation statements)
references
References 20 publications
10
73
0
Order By: Relevance
“…Consistent with this, inhibition of MEK was demonstrated to enhance basal-and LH-stimulated StAR expression, but attenuate steroid synthesis both in primary and in mouse Leydig tumor cells (Martinat et al 2005), an observation in agreement with IGF-I responsive steroidogenesis (Manna et al 2006). MEK inhibition has also been associated with hCG-responsive decrease (Gyles et al 2001, Martinelle et al 2004) and LH/FSH-mediated increase (Seger et al 2001, Tajima et al 2003 in StAR expression and steroid synthesis in gonadal cells. We have previously demonstrated that inhibition of MEK was capable of decreasing EGF-and (Bu) 2 cAMP-responsive StAR expression and steroid synthesis in mouse Leydig cells (Manna et al 2002a).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Consistent with this, inhibition of MEK was demonstrated to enhance basal-and LH-stimulated StAR expression, but attenuate steroid synthesis both in primary and in mouse Leydig tumor cells (Martinat et al 2005), an observation in agreement with IGF-I responsive steroidogenesis (Manna et al 2006). MEK inhibition has also been associated with hCG-responsive decrease (Gyles et al 2001, Martinelle et al 2004) and LH/FSH-mediated increase (Seger et al 2001, Tajima et al 2003 in StAR expression and steroid synthesis in gonadal cells. We have previously demonstrated that inhibition of MEK was capable of decreasing EGF-and (Bu) 2 cAMP-responsive StAR expression and steroid synthesis in mouse Leydig cells (Manna et al 2002a).…”
Section: Discussionsupporting
confidence: 69%
“…In addition, longer-term incubation with cAMP-independent factors in mLTC-1 cells was associated with positive (IGF-I and FGF) and negative (EGF, IL-1, and CSF-1) effects on [ Conflicting results for the role of the MAPK/ERK signaling cascade in regulating StAR expression and steroidogenesis in different steroidogenic cells have been demonstrated (Gyles et al 2001, Seger et al 2001, Tai et al 2001, Dewi et al 2002, Manna et al 2002a, 2006, Seto-Young et al 2003, Tajima et al 2003, Martinelle et al 2004. For example, inhibition of MAPK/ERK (MEK) activity with PD98059 and U0126 has been shown to be associated with stimulation (Seger et al 2001, Tajima et al 2003, inhibition (Gyles et al 2001, Manna et al 2002a, Martinelle et al 2004, or no effect (Tai et al 2001, Seto-Young et al 2003, Tajima et al 2005) on the steroidogenic response. In the present study, different factors were found to stimulate MAPK signaling to various levels as determined using a pathdetect Elk-1 trans-reporting assay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that LH treatment increased ERK1/2 phosphorylation in a dose-and timedependent manner. A role for MAPK/ERK signaling in regulating gonadotropin-induced steroidogenesis in mammalian and avian granulosa cells (Moore et al 2001, Seger et al 2001, Dewi et al 2002, Cottom et al 2003, Su et al 2006, Woods & Johnson 2007 and in rat Leydig cells (Martinelle et al 2004) has also been reported. Although LH-induced P 4 synthesis by the mouse/rat uteri has been documented earlier (Bonnamy et al 1989, Mukherjee et al 1994, Debnath et al 2000, little is known about its mechanism of action.…”
Section: Discussionmentioning
confidence: 96%
“…We further observed that LH-stimulated ERK1/2 phosphorylation leading to increased P 4 production is significantly inhibited by PD98059, suggesting that action of LH on ERK1/2 phosphorylation is mediated by upstream MEK1/2. Although involvement of MAPK in mediating gonadotropin-stimulated steroidogenesis has been observed in many species, conflicting results in different steroidogenic tissues have been demonstrated (Seger et al 2001, Dewi et al 2002, Manna et al 2002, Seto-Young et al 2003, Martinelle et al 2004, Tajima et al 2005. For example, inhibition of MAPK/ERK1/2 activity with PD98059 and U0126 has been shown to be associated with stimulation (Seger et al 2001, Tajima et al 2003, inhibition (Gyles et al 2001, Manna et al 2002, Martinelle et al 2004, or no effect (Tai et al 2001, Seto-Young et al 2003, Tajima et al 2005) on steroidogenic response.…”
Section: Discussionmentioning
confidence: 99%